Kritik Fakhruddin al-Razi terhadap Emanasi Ibnu Sina - Imron Mustofa (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2015)
In order to uncover the existence of this universe, human will find two man theories about how God created this universe: Theory of Emanation and Theory of Creation. In the view of Theory of Emanation, this universe was transmitted from the Transcendent Being trough a hierarchical levels; while Theory of Creation taught that the beginning of universe as the creation of The One Almighty God. It is interesting that every single opinion have their argumentation supported by number of famous philosopher, such as Ibn Sina who supported Theory of Emanation, and Fakhruddin al-Razi who refuted that idea and declared that Theory of Creation is more legitimate. Ibn Sina’s theory evidently was an improvement from the theory of movement owned by Aristotle. According to this theory, every entity has potential and action aspect. Movement is the process from the potential to the action, and its process can take place because of supporting cause. These causes led finally to the Prime Cause defined as unmoved mover. In the perspective of Ibn Sina, this ‘Prime Cause’ is God that Wajib al-Wujud. Wajib al-Wujud led later to the main argument of Ibn Sina about the existence of God. Al-Razi did not agree with Ibn Sina’s theory. From here, al-Razi launched his criticism against Ibn Sina’s thought about the Theory of Emanation. This paper will discuss further about al-Razi’s critique toward Ibnu Sina’s concept of God which focusced on the theory of movement and singularity.